Análisis Financiero de la empresa Ediloja Cía. Ltda., de la ciudad de Loja periodo 2022-2023 - Castillo Ordoñez, Natalia Anai (2024)
Financial analysis is a key tool for evaluating the economic health of a company. The current research entitled “Financial Analysis in the Company Ediloja Cía. Ltda. of the city of Loja period 2022-2023”, was developed to achieve the main purpose as the secondary goal of creating a financial analysis in the Company Ediloja Cía. Ltda. of the period 2022-2023. To achieve the proposed objectives, vertical and horizontal analysis was applied, along with calculating the main financial indicators of liquidity, profitability, debt, and activity of the financial statements of Ediloja Cia. Ltda. Regarding the vertical and horizontal analysis, it was identified that the company manifests an asset structure focused on current assets, with 78,84% and 67,57% in 2022 and 2023, respectively. As an optimization of these accounts, while most of the current assets (38,42%) were concentrated in tax assets in 2022, by 2023 the company collected these accumulated assets, making the cash and its equivalents account the most significant in this period at 41,40%. On the other hand, liability, and assets are almost entirely concentrated in liabilities, especially in non-current liabilities, accounting for 48,07% (2022) and 52,04% (2023), with employee benefits being particularly noteworthy. Meanwhile, equity represented only 7,64% and 3,80% respectively, demonstrating the dependence of the company on external debt. In terms of its economic activity, Ediloja Cia. Ltda. reveals an optimal level of operating income, increasing by 10,44%. However, despite good sales levels, expenses have increased, especially with a 9,64% rise in employee benefit expenses, leading to a decrease in profit from $16.123,77 (2022) to $13.879,07 (2023). In the application of financial indicators, Ediloja Cia. Ltda. demonstrated an optimal liquidity level, with a current ratio of 1,69 in 2022 and 1,53 in 2023. Additionally, it achieved good results in its receivable turnover, with a 29-day collection period in 2022 and 36 days in 2023. This was accompanied by an optimal sales turnover ratio, indicating the company generated more than twice its assets in sales during both years, with results of 2,49 and 2,30 respectively. However, the debt levels obtained reveal a considerable reliance on long-term liabilities, leaving a reduced profitability margin for Ediloja Cia. Ltda., posting results of 0,01 in both periods for both its net and operating margins. However, although Ediloja Cia. Ltda. demonstrates sufficient solvency to meet short-term obligations, it faces challenges related to debt and profitability that may affect its long-term financial stability. The financial analysis report will enable an assessment of the results from the applied analysis and indicators, reflecting the economic reality of Ediloja Cia. Ltda. for the studied period 2022- 5 2023. Accompanied by the resulting conclusions and recommendations, this study will serve as a decision-making tool to improve the economic and financial health of the company.